Study of hearing impairment and chronic otitis media in school going children in Pokhara, Nepal - Byanju, Jayandra; Saha, Chhanchu Gopal (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Hearing loss and chronic otitis media among school-aged children in developing countries is reported to be a significant health problem. This problem in children influences the overall development of behavioral and communication skills. The main objective of this study was to study the hearing impairment and chronic otitis media in school going children in Pokhara. Methods: This was a cross sectional study done in Pokhara district, Kaski, Western Region Nepal in two private schools and one government school of Pokhara, selected randomly. All these children were interviewed for history taking and the examinations included tuning fork examination (Rinne’s, Weber’s and absolute bone conduction tests) and examination of the ear using otoscope. Results: A total of 215 school children were included in the study. The mean age was 12.04 (SD=1.108), male 48.4% and female 51.6%. Hearing impairment was found in 21.4% and chronic otitis media in 9.8%. Among hearing impairment, 71.7% had conductive and 28.3% had sensorineural type of hearing losses. Out of total number of children, 12.1% had tympanic membrane perforation. Conclusions: The prevalence of hearing impairment was seen in one fifth and chronic otitis media in one tenth of local school children of Pokhara city, Nepal. Country wide prevalence and causes for preventive measures should be studied.